Service Quality of Islamic Banks: A Cultural Perspective - Hanafi, Siti Nurul Izzati Mohd; Maulan, Suharni Bt.; Hamid, Siti Ngayesah Ab. (International Journal of Islamic Banking and Finance Research, 2020)
The purpose of this paper is to examine the relationship between culturally-based service quality measure on customer satisfaction and loyalty in the Malaysian Islamic banking context. This study utilises the PAKSERV model, a cultural-based instrument together with additional dimensions compliance from CARTER model. A survey questionnaire was utilised to examine the relationships. Data were analysed using PLS-SEM. The result shows that five of the service quality dimensions have significant relationships with customer satisfaction. Compliance, the additional dimension, had been found to be the most influential. This study also reinforces the relationship between satisfaction and loyalty. The compliance dimension added to the PAKSERV measure that denotes religious belief enhances the cultural elements of service quality measure for Islamic banks.